Analysis of the Reciprocity of Bilateral Relations between Indonesia and Brazil in 2014 – 2021 - Pratiwi, Cahayu Anggita; Yunita, Primadiana (Andalas Journal of International Studies (AJIS), 2023)
The longstanding trade relationship between Indonesia and Brazil suggests potential reciprocity in their bilateral interactions, primarily driven by significant trade activities in sectors such as agriculture and manufacturing, which are crucial for robust international cooperation. This study employs the cooperation hexagon concept and uses a descriptive qualitative method to examine the bilateral trade cooperation between Indonesia and Brazil from 2014 to 2021, assessing the reciprocity in the relationship dynamics. The analysis reveals an absence of reciprocity, particularly in the areas of trust and mutual benefits, highlighting a systematic failure to meet crucial cooperation variables. Despite the historical continuity of these relations, the findings emphasize an urgent need for Indonesia to intensify efforts to build more effective cooperation with Brazil. Enhancing this cooperation could leverage mutual benefits and strategic alignments, which are essential for addressing contemporary global challenges and opportunities.